PEMBUATAN SEDIAAN OLES EKSTRAK KENTAL DAUN BINAHONG (Anrederacordifolia (Ten.) Steenis) DAN MADU SEBAGAI PERAWATAN LUKA LUAR - Herawati, Desri; Putra, Risa Kota; Farhan, Farhan (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Backgroud: All parts of the Binahong plant (Anredera cordifolia (Ten.) Steenis) from the roots, tubers, stems, leaves and flowers are very effective for herbal therapy. Especially of the leaves Binahong plant (Anredera cordifolia (Ten.) Steenis) can used to treatment of open wounds.The aim: This study aims to provide from pharmacetical stock to traditional herb that can be used to prevent a disease and to improve health by community by society. Method: This research is descriptive method developed from the previous research studied about the efficacy of Binahong leaves (Bassela rubra linn, or Heartleaf maderavine madevine) for curing wound on skin. In this study, the researcher provide pharmacetical stock of Binahong leaves in condensed extract form mixed with honey as wound treatment on skin. The process of pharmacetical stock used soxhlet method, extraction with organic solvents is done repeatedly and keeping constant the amount of solvent, and calculate the yield for three days. The solution used in this process is Ethanol 96% with 500 cc. The solution extract got from this process is 400 cc with yield 24.29%. The making of pharmacetical stock was done by adding 28 cc honey to 12.145 gr condenced extract. Then, the mixture is polished. Next process, the pharmacetical stocks are divided into four pot with each pot is 15 gr. The content of the pharmacetical stock of each pot is 2,46 gr condenced extract of the Binahong leaves and 7.7 cc honey. Result: Organoleptic test is done for three week. The result is there is no negative change happened viewed by form, colour, odour, and tastes and mushroom growt as well. Conclusion: The research successfuly made the pharmacetical stock in condenced extract with expire date for three week.